Metode dan Ideologi Penerjemahan Kotowaza dalam Blog Kursus Bahasa Jepang Evergreen - Weliantari, Ni Ketut Suni (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 2 No 2 (2020)DO - 10.24843/JS.2020.v02.i02.p05, 2020)
This study is aimed at identifying the type of translation methods and their application in translating kotowaza on the Japanese Course blog Evergreen. The data were obtained by using observation method and note-taking technique. Furthermore, the analysis of the data was done by applying the translational identity method and glossing technique. The theory of translation methods by Newmark (1988) was also used in this study. The result shows that the translation of 40 kotowaza on the Japanese Course blog Evergreen use only four from eight translation methods proposed by Newmark. Based on its translation methods, the study found out that 13 data use literal translation, 9 data use adaptation, 14 data use the free translation, and 4 data use communicative translation. Kotowaza that has an equivalent in Indonesian proverb tends to be translated by using adaptation and communicative translation. However, not all kotowaza are equivalent to Indonesian proverbs with both of those methods. In this case, using literal translation is another way of translating kotowaza. Meanwhile, kotowaza which its equivalent cannot be found in Indonesian proverb is translated with literal translation or free translation.